Semiotics of “Name Calling” in Propaganda Discourse - AAl-Bheish, Raja Ahmed (ALBAHITH ALALAMI, 2012)
The process of name calling in the propaganda discourse is one of the most important methods of persuasive propaganda act, based on the ideology of working with the function, and the valuation of this function, creating a hermeneutic representation of the meaning falls within a specific format and responds to a specific function, which is the realization of the intent of the propaganda doer in persuasion and persuasion through negative and positive propaganda logic. The method of name calling has played a dangerous and horrific role in conflicts and ideological and military wars throughout history.This study aims to find out the mechanisms of semiotics system behind discourse of propaganda far from substantive sample - the Empirical Method based on description and silencing of communicative messages.The research adopted the definition of discourse as a basis for determining its concept and definition of the subject and identified the mechanisms of name discourse function through representing reality with linguistic codes based on the two basic types are argumentative and metonymy fallacies. The researcher, then, used logical errors and stereotypes; and created the relationship of semantic necessity; and visioning discourse through historical symbols and contemporary symbols where the mechanisms and laws, the designation of names, were identified in the symbolism of propaganda discourse. This study set the philosophy of the calling names as a fundamental dimension. The study, moreover, did not overlook propaganda applications, but was keen on them to demonstrate the mechanisms and laws of stylistic function of calling names in the propaganda process. With supporting such process in terms of the choices of the propaganda doer and strategies of the process of receiving by the public.We hope in this approach of research in semiotics of communication to go out of the “paradigm” of quantitative research which has been left by most of the American researches since the early eighties. But this kind of research remained dominant in the Arab world through the Egyptian school without researchers and media attention that the studies of critical approach in the analysis of discourse are the beginning of the way towards new media.